2012
DOI: 10.1007/s00403-012-1264-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential cytotoxic response in keloid fibroblasts exposed to photodynamic therapy is dependent on photosensitiser precursor, fluence and location of fibroblasts within the lesion

Abstract: Treatment of keloid disease (KD) is ill-defined and remains challenging. We previously reported successful clinical application of photodynamic therapy (PDT) in KD. The aim here was to evaluate cytotoxic effect of PDT using methyl aminolevulinate (M-ALA) and 5-aminolevulinic acid (5-ALA) on keloid fibroblasts (KF) (n = 8) from different lesional sites (top, middle and margin) as compared to normal skin fibroblasts (n = 3). The effect of protoporphyrin IX (PpIX) precursors was evaluated by fluorescence emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…This was subsequently illuminated with a PDT machine (Omnilux PDT, Photo Therapeutics, PA), with an arrangement of red light‐emitting diodes (LEDs) of 633 ± 3 nm wavelength. The power intensity of the PDT machine was adjusted to 20 J/cm 2 and calibrated with an IL1700 radiometer (International Light Technologies Inc, Peabody, MA) . PDT treatment was given once on the third day after collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was subsequently illuminated with a PDT machine (Omnilux PDT, Photo Therapeutics, PA), with an arrangement of red light‐emitting diodes (LEDs) of 633 ± 3 nm wavelength. The power intensity of the PDT machine was adjusted to 20 J/cm 2 and calibrated with an IL1700 radiometer (International Light Technologies Inc, Peabody, MA) . PDT treatment was given once on the third day after collection.…”
Section: Methodsmentioning
confidence: 99%
“…PDT works by energy transfer from illumination to molecular oxygen through the action of a photosensitizer, 5‐aminolevulonic acid (5‐ALA), as precursor of protoporphyrin IX. Cellular effects of PDT depend on tissue type, oxygen tension and dosage, resulting in necrosis, apoptosis, and autophagy …”
mentioning
confidence: 99%
“…Keloids are a type of scar formed from fibroproliferative dermal tissue characterized by the excessive proliferation of fibroblasts. Mendoza et al [47] evaluated the cytotoxic effects of PDT using MAL and ALA on KD fibroblasts compared to normal skin fibroblasts. Li et al [48] investigated the effects of ALA-PDT and showed that hypertrophic scar-derived fibroblasts accumulated more PpIX.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…74 This study showed that the outcome of PDT was dependent on the photosensitizer precursor, the fluence and the location of fibroblasts in the lesion. A positive effect of PDT was initially reported in a patient with a persistent keloid that had not responded to a number of routine therapies.…”
Section: Photodynamic Therapymentioning
confidence: 99%